2018
DOI: 10.1111/ctr.13208
|View full text |Cite
|
Sign up to set email alerts
|

Complement system in lung transplantation

Abstract: The complement system is a cascade of multiple proteins that have been known to mediate inflammatory response. This tightly regulated system has been recognized to play a role in adaptive immunity via humoral and cell-mediated processes. There is evidence from animal and human studies that the complement system is involved in various outcomes of solid organ transplantation. Most of the studies have been done in the field of kidney transplantation. In this paper, we review the studies looking at lung transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…While the role of complement activation in acute lung injury has been evaluated in both experimental ( 16 ) and clinical settings ( 25 , 26 ), its role in lung allograft injury is only beginning to be explored ( 27 , 28 ). While targeting the complement cascade has been successful in certain preclinical models ( 29 31 ), follow-up studies have been met with tempered enthusiasm, despite moderate success in clinical trials ( 20 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the role of complement activation in acute lung injury has been evaluated in both experimental ( 16 ) and clinical settings ( 25 , 26 ), its role in lung allograft injury is only beginning to be explored ( 27 , 28 ). While targeting the complement cascade has been successful in certain preclinical models ( 29 31 ), follow-up studies have been met with tempered enthusiasm, despite moderate success in clinical trials ( 20 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that C3(H 2 O) increases in the BAL fluid of lung transplant recipients prior to the development AMR. While complement activation has been connected with AMR (46, 47, 49), C4d staining in lung of AMR patients is neither sensitive nor specific, and an entity of C4d-negative AMR is also increasingly appreciated (48). Moreover, C4d staining needs a biopsy to be performed, and is most likely to be positive around the time of AMR diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, targeted SNP analyses focused on the role of the complement system in solid organ transplantation have increased (4, 39, 40). Our group previously reported a genetic promoter polymorphism in several complement regulatory proteins to be associated with chronic rejection after LTx (41), and with kidney transplant outcome (42).…”
Section: Discussionmentioning
confidence: 99%
“…In solid organ transplantation, complement proteins play an important role in both acute, and chronic rejection (4). In a prospective cohort study it was shown that increased levels of complement proteins C4a and C5a early after LTx were associated with primary graft dysfunction (5).…”
Section: Introductionmentioning
confidence: 99%